Research dynamics and frontier trends of orogenic gold deposits: a knowledge map based on bibliometrics - Liu, KeXin; Jiang, Nan; Zhang, YongQiang (Frontiers in Earth Science, 2025)
Orogenic gold deposits represent a vital component of global gold reserves, functioning as both significant sources of gold and essential indicators for understanding crustal metallogeny within collisional tectonic environments. This study employs bibliometric analysis on 2,476 publications sourced from the Web of Science Core Collection (1995–2025) to delineate the intellectual evolution and emerging frontiers in orogenic gold research. Through systematic examination utilizing Citespace and Vosviewer, we identify publication trends, geographic distribution, institutional contributions, and citation networks of global orogenic gold deposit studies. Key findings reveal concentrated research output from China (1,031 papers), Australia (626 papers), and Canada (326 papers), with the China University of Geosciences and the University of Western Australia emerging as prominent institutional hubs. While Deng Jun and Santosh M. lead contemporary productivity metrics, foundational contributions by Groves DI (3,459 citations) and Goldfarb RJ (4,590 citations) continue to serve as pivotal citation anchors. Based on the analysis, the research frontiers should focus on three key areas: (1) Cross-scale mineralization mechanism studies, including numerical simulations of supercritical fluid (H2O-CO2 ± CH4) phase behavior, four-dimensional visualization reconstruction of lithospheric material cycles, and quantitative analysis of pressure-driven (∼150 MPa) phase transitions and adsorption kinetics in sulfide-mantle fluid coupling mechanisms; (2) Technological and methodological advancements, emphasizing the development of AI-powered three-dimensional orebody prediction models and the establishment of deep exploration technology consortia capable of penetrating up to 8 km; (3) Theoretical paradigm shifts, promoting the integration of micro-area isotopic tracing techniques with deep dynamic models to elucidate the control mechanisms of supercontinent cycles on the spatiotemporal architecture of mineralization systems. This field is transitioning from empirical exploration toward a theory-driven research paradigm.